2020
DOI: 10.1159/000507294
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship between MR-Based Supraclavicular Fat Fraction and Thyroid Hormones

Abstract: Purpose: Brown adipose tissue (BAT) plays a potential role in energy and glucose metabolism in humans. Thyroid hormones (TH) are main regulators of BAT development and function. However, it remains unknown how the magnetic resonance (MR)-based proton density fat fraction (PDFF) of supraclavicular adipose tissue used as a surrogate marker for BAT presence relates to TH. Therefore, the purpose of this analysis was to investigate the relationship between supraclavicular PDFF and serum levels of TH. Methods: In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In our previous study, we had reported that FT3 level at baseline was significantly higher in BAT-positive healthy participants than BAT-negative participants 56 . Junker et al 57 reported biologically active T3 may be involved in the development of supraclavicular BAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we had reported that FT3 level at baseline was significantly higher in BAT-positive healthy participants than BAT-negative participants 56 . Junker et al 57 reported biologically active T3 may be involved in the development of supraclavicular BAT.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we had reported that FT3 level at baseline was significantly higher in BAT-positive healthy participants than BAT-negative participants ( 55 ). Junker et al ( 56 ) reported that biologically active T3 may be involved in the development of supraclavicular BAT. In our current study, we also found that circulating FT3 concentration was significantly higher in BAT-positive patients compared to BAT-negative patients in both the hyperthyroid and euthyroid states.…”
Section: Discussionmentioning
confidence: 99%
“…However, these acute changes in circulating T4 and TSH levels are of unclear clinical significance. Higher serum T3 levels were found in cold-induced 18 FDG BAT–positive individuals in one study ( 406 ) and with lower BAT fat fraction on MRI in another ( 408 ). A positive association between serum free T4 levels and cold-induced BAT glucose uptake was found in 24 euthyroid and healthy participants ( 409 ).…”
Section: Regulation Of Brown Adipose Tissue Activity and Capacitymentioning
confidence: 92%
“…To explore the roles of LBP in adipose browning and metabolism, MEFs were induced to differentiate into adipocytes with BAT-like characteristics, and the transfection of shLBP was made to establish the model of gene silence at the same time. Located in mitochondria, UCP-1 is a characteristic protein of BAT, which fulfills a crucial function on the release of energy in the form of heat (thermogenesis) through uncoupling oxidative phosphorylation from synthesized adenosine triphosphate (ATP) [ 49 ]. A prominent upregulation of the UCP-1 level has been exhibited in LBP-null mice and adipocytes treated with the silence of LBP [ 40 ].…”
Section: Discussionmentioning
confidence: 99%